Introducing Creative City Factors as a Solution in Sustainable Urban Development: A Case Study from Bushehr City in Iran - Tayebeh, Pourbeh; Gholamreza, Jafarinia; Ali, Shamsoddini; Jafarpour Ghalehteimouri, Kamran (Journal of Urban Culture Research, 2023)
Bushehr city is located in one of the provinces rich in both oil and in historical sites with an international port on Persian Gulf. However, it has never been successful in terms of sustainable development and planning. Therefore, this study aims to identify the effective factors in constructing a creative city, as well as its relationship to Bushehr’s sustainable urban development. The primary data was collected over the course of 18 years, and the Cochran formula was used to determine the exact size of the statistical population, which was 384 people. Pearson’s correlation coefficient, path analysis, and regression analysis were used to analyze the data with SPSS software. Creative cities and sustainable urban development have a Pearson correlation coefficient of 0.468. The independent variables explain and predict 35.5% of the variance in sustainable urban development in multivariate regression analysis. The creativity and innovation variable, as well as the quality of life, have the most BETA.